The American dream and the public schools - Hochschild, Jennifer L., 1950-; Scovronick, Nathan B., 1945- (Oxford University Press, 2004)
... Examines ... desegregation, school funding, testing, vouchers, bilingual education, multicultural education, and ability grouping. These seem to be separate problems, but much of the contention over them comes down to the same thing: an apparent conflict ... between policies designed to promote each student's ability to pursue success and those designed to insure the good of all students or the nation as a whole. The authors show how polices to promote individual success too often benefit only those already privileged by race or class ... The book also examines issues such as creationism and afrocentrism ...